Clinical outcomes of elective single morula embryo transfer versus elective single blastocyst embryo transfer in IVF-ET - Kang, Sang Min (Springer US, 2012)
PURPOSE: To compare the clinical outcomes of elective single morula embryo transfer (eSMET) versus elective single blastocyst embryo transfer (eSBET) in selected patients. METHODS: This study was a retrospective study which analyzed for 271 cycles in women under 37 years of age who are undergoing their first or second trial of in vitro fertilization-embryo transfer (IVF-ET) from January 2008 to December 2009. The eSMET was performed on day 4 (n = 130) and the eSBET was conducted on day 5 (n = 141). RESULTS: The clinical pregnancy rate (51.5% vs. 51.8%, p = 0.97), implantation rate (52.3% vs. 52.5%, p = 0.98), and live birth rate (39.2% vs. 44.7%, p = 0.36) were similar in the eSMET and eSBET groups, respectively. The miscarriage rate of the eSMET group (23.9%) was slightly higher than that of the eSBET group (13.7%) (p = 0.12), without reaching statistical significance. There was only one case of monozygotic twin pregnancy in each group. CONCLUSIONS: The clinical outcomes of day 4 eSMET were comparable to those of day 5 eSBET. Therefore, day 4 eSMET is a viable option or an alternative to day 5 eSBET, with no difference in success rates.